Improving Thermal Comfort and Air Quality: PET and CO₂ Evaluation of School Courtyard’s Orientation - Salameh, Muna; Touqan, Basim (Salehan Institute of Higher Education, 2025)
This study aims to investigate the thermal conditions related to the variations in the school courtyard’s orientation, focusing on mass temperature (Tm), outdoor air temperature, and Physiological Equivalent Temperature (PET). A qualitative methodology based on ENVI-met software was adopted. Simulations for the existing school building were performed in the four basic orientations on 21 March and 21 September to assess the thermal impact of the courtyard’s orientations. Results showed that orientation produced slight but meaningful differences in Tm, with variations of 0.16°C in September and 0.20°C in March. Though modest, these differences become significant when scaled to the large mass of the school buildings, where even small reductions affect energy demand and comfort. For outdoor air temperature, the south orientation achieved reductions of 0.53–1.13°C in September and 1.1–1.9°C in March compared to ambient conditions. PET and wind maps supported these findings, with the south orientation allowing better airflow and better thermal comfort. Furthermore, analysis of CO₂ concentration confirmed that the south-facing courtyard provided the healthiest air quality. The study highlights that courtyard orientation should not be overlooked in large educational buildings, as even slight orientation-driven improvements become critical, reinforcing the importance of integrating orientation into holistic passive design strategies.